English for Culinary Major in Vocational High School: The Prototype - Ardhi Eka Fadilah; Raisha Nur Anggraini (Journal of English Language Teaching and English Linguistics, 2025)
English language subject which is taught in Vocational High School does not seem suitable with the needs of the students who study in specific field of study, especially in culinary. Based on this current situation, the present research and development study developed English materials for culinary students by using skill-based approach in which it includes the objective of performance and competence accomplishments. Began with needs analysis process, it was done before the development of the materials and it was conducted in SMKN 3 Malang. The needs analysis is aimed at finding the students’ needs toward English for culinary major and the target students were the tenth graders who are taking culinary major. The steps in this needs analysis were determining the instruments to collect the data, designing the blueprint of the instruments, constructing the instruments based on the blueprints, collecting the data in the field, and analyzing the data. In these current needs analysis, two instruments will be used, namely questionnaire and interview. Thus, the final product of these English materials for culinary purpose is expected to give fruitful contribution in the future for both teacher and student during the teaching and learning process of English language.